Optimizing Digital Transformation Services Through the E-Tilang App at the Majalengka District Attorney’s Office - Crisna Satria Febriana; Sri Wulandari (Journal of Comprehensive Science, 2026)
Technological advancements have prompted many government agencies to prioritize the use of electronic systems in implementing their work programs. One such agency is the Majalengka District Attorney's Office, which utilizes the E-Tilang application for traffic violation services, aiming to make the handling of traffic violations more efficient and transparent. This study aims to analyze the digital transformation services provided through the E-Tilang application at the Majalengka District Attorney's Office with regard to traffic fine payments and the retrieval of seized evidence. The research method used is qualitative descriptive, employing data collection techniques of observation, interviews, and documentation, within the E-ServQual framework, which encompasses Efficiency, Fulfillment of Needs, Responsiveness, Compensation, Contact, and Privacy. The results indicate that the implementation of the E-Tilang service provides significant convenience and efficiency for the public. Challenges include technical issues such as system disruptions during implementation and the fact that not all members of the public have fully adopted mobile banking for digital payments; however, the E-Tilang service continues to operate effectively, albeit not yet at optimal levels. The E-Tilang service program has successfully established a reliable service; however, to optimize the application, strengthening is needed in the digital and humanware (human resources) aspects in order to achieve the highest possible quality of digital transformation services, as well as continuous direct and indirect outreach in both urban and rural areas through social media.